Analysis of tapered work roll shifting technique in 5-stand UCMW tandem cold rolling process. Issue 3 (27th May 2021) - Feng, Xiawei; Wang, Xiaochen; Sun, Jiquan; Yang, Quan
ABSTRACT: Producing strips that are as flat and wide as possible is the forever quest of rolling industry. Tapered work roll shifting technique is effective to reduce edge drop, but results in a rigid roll stack and strip breaks. These detrimental phenomena can be avoided by intensive parametric study and industrial experiences. By advancing a well-established analytical method, an intensive simulation campaign is conducted to reveal the effectiveness of tapered work roll shifting in the context of 5-stand six-high cold tandem rolling process. The effects of bending and shifting of work roll and intermediate roll on edge drop and profile have been discussed. The roll stack becomes the most rigid at the 2nd stand, which calls for extra intermediate roll shifting to prevent strip break. Both the control abilities of work roll bending and intermediate roll bending on edge drop and strip crown is greatly enlarged by work roll shifting technique. The heredity of strip profile is the strongest at the last stand, and it is more effective to change strip shape at the upstream stands. Industrial trial experiments are also presented in order to solve the interfering problem of strip profile, flatness and surface quality.